2015
DOI: 10.1097/maj.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Inflammation in ST-Segment Elevation Myocardial Infarction

Abstract: Abstract:Background:To investigate the factors predicting the onset of major adverse cardiovascular events (MACEs) after primary percutaneous coronary intervention for ST-segment elevation myocardial infarction (STEMI) patients.Methods:Two hundred forty-eight STEMI patients (61.4 ± 10.8 years, 186 men) who underwent successful primary percutaneous coronary intervention were enrolled. Patients were followed-up for 1 year. Univariate, multivariate analyses, and receiver operating characteristic curve analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Our results concur with a burgeoning evidence that baseline hemoglobin measurements improve the prognostic ability of the GRACE score with regards to in-hospital and 30-day mortality [31][32][33], death/MI within 6 months [34,35] or MACEs within 12 months [36]. None of these studies, however, are from a rural setting and have reported prevalence of baseline anemia to be <30%.…”
Section: Discussionsupporting
confidence: 88%
“…Our results concur with a burgeoning evidence that baseline hemoglobin measurements improve the prognostic ability of the GRACE score with regards to in-hospital and 30-day mortality [31][32][33], death/MI within 6 months [34,35] or MACEs within 12 months [36]. None of these studies, however, are from a rural setting and have reported prevalence of baseline anemia to be <30%.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to thrombosis and platelet activation, a number of studies suggest that inflammatory response also plays an important role in the occurrence and progression of STEMI. [35]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an increased NLR results in more vulnerable plaque and higher risk of thrombotic diseases . A follow‐up investigation of 248 patients who underwent primary percutaneous coronary intervention with ST‐segment elevation myocardial infarction reported that 36 patients experienced major adverse cardiovascular events . The authors concluded that higher NLR and lower hemoglobin independently predicted 1‐year major adverse cardiac events …”
Section: Introductionmentioning
confidence: 99%